Primary Breast Burkitt Lymphoma: Case Report - Ferreira, Laís Gomes (2022)
Introduction: Primary breast lymphoma (PML) represents about 0.5% of breast cancers, being considered a rare type of tumor. Some of the types of PML, in turn, have an intense connection with the pregnancy and postpartum period due to hormonal stimulation. The aim of this study is to report a case of PML with a rare presentation of Burkitt’s lymphoma, considering effective therapeutic proposals for follow-up. Case report: A 23-year-old female patient with a peri-areolar tumor in the right breast with orange peel aspect and rapid growth for one month, phlogistic complaints at the lesion site, good general condition and no other associated symptoms. The reported condition started seven months after fetal expulsion with a dead fetus. The patient underwent lesion biopsy and was referred to an outpatient follow-up with unsuccessful outcome, requiring return to the hospital due to worsening of clinical conditions and extension of the tumor. There was a diagnosis of Burkitt’s lymphoma, with multidisciplinary treatment. She underwent the CODOX-M chemotherapy protocol, and died after 22 days of hospital follow-up. Conclusion: This report demonstrates a rare situation in a young patient, emphasizing the importance of effective investigation of breast changes so that correct early diagnosis and appropriate treatment can be made for all age groups.